APPLICATION OF ROLE PLAYING TECHNIQUES IN THE CONTEXT OF GROUP COACHING - All Habsy, Bakhrudin; Valencya, Natasalwa; Mayassary, Zilfy Nurillah; Linsetyowati, Nabita Cahya Camilla; Ramadhani, Karina Putri (PT Altin Riset Publishing, 2024)
Group guidance the role-playing technique is one of the services that plays a role in preventing problems and difficulties for students in the scope of their personal, social, academic, and learning lives. Group guidance role-playing techniques can help learners develop their personal abilities and potential, make decisions, and choose a career in a dynamic group. This study aims to describe in depth the role-playing technique in the context of group guidance. This study employs a qualitative research design, drawing upon the literature study method. Accredited national and international journals provided books and articles as data sources. The results of the study include: (1) the concept and purpose of applying role playing techniques in the context of group guidance, (2) the stages of implementing group guidance role playing techniques, and (3) the advantages and disadvantages of role playing techniques in group guidance.